Atividade minerária, barragens e o poder de polícia do Estado: limites das responsabilidades - Araujo, Flavia Möller David (2020)
Nowadays, mining activities are essential in our routines. It is an activity regulated by the Federal Constitution, deeming minerals are considered assets of the Federal Union and their economic exploitation is duly regulated by ordinary laws considering the constitutional values established. The protection of the environment is also constitutionally protected and regulated by common laws. It is possible to establish that there shall be a possible conflict between mining and the environment protection. It is part of the role developed by the public authorities to organize the activity, aiming this conflict to be as minimum as possible, and duly protecting environmental and mineral assets. In 2015 and 2019, we have faced two major accidents involving mining dams, with great loss of lives and unimaginable damages for the environment. These events caught attention for possible responsibilities involved in these accidents. However, considering the State’s monopoly and public authority for custody and protection of public interests, as well as the competencies assumed by them, by means of administrative police power, we intend to verify and demonstrate that this respective responsibility could also be shared with the Public Administration. This study proposes to analyze the matter of the mining dams monitoring system within the verification of due exercise of policing power. It is sought to comprehend, in all its phases, starting from the publication of regulatory norms, fixating criteria, if those were respected, searching for the equilibrium of relations. All this process (and not the specific cases) shall be the object of this study. The proposition is to verify the process as a whole. It does not mean that there shall be any exclusion of responsibility. The result could be turning one party or another party accountable; or share such responsibility, in equal parts or not. It is not possible, however, to focus solely on the mining companies’ duties. The thesis object, then, is the rejection of the initial mediatic conclusions of a serious accident of great cost, exchanging it for an analysis of all competences and actors involved. With that said, we propose a solid and equidistant evaluation of the whole process and the factors involved in the mining dam’s safety investigations, and not just an automatic imputation of responsibility. The utilized methodology in the present work contemplated extensive bibliographic research regarding the theme, legislative info-gathering of the national normative acts pertaining dam’s safety (i.e. laws, decrees, ordinances, resolutions etc.), as well as the gathering of journalistic material of the mediatic impact related to the mineral dam’s accidents. The conclusion can be the withdrawal of apparent full responsibility to a particular entity and a possible sharing of the latter with the Public Administration